DFMA Method: Analysis on a Bananas Getuk Mixer and Moulding Machine - Aurel Maydivi Salsabilla; Anda Iviana Juniani; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
The process equipment for the Bananas Getuk machine production, which initially used manual and hand tools, began to be developed for production machine designs, including a mixer machine and a banana Getuk molding. The Bananas Getuk Mixer and Molding Machine used today needs fixing in production. Namely, there is still dough left in the machine, and there are detached components. This problem has an impact on the ineffectiveness of production time and costs. This study aims to analyze the design of the machine by utilizing the DFMA method. The DFMA method provides an assembly process efficiency index (DFA Index) and recommendations for design improvements without changing the machine's function. The results of the DFMA analysis on the Bananas Getuk Mixer and Molding Machine resulted in a DFA Index value of 5.0 and design improvements that included the frame, mixing container, mixer, coaster, hopper, extruder, and bulkhead to increase the efficiency value of the machine.